Oxidation of norbornene over vanadium-substituted phosphomolybdic acid catalysts and spectroscopic investigations - Raj, N. K. K.; Ramaswamy, A.; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2005)
Oxidation of norbornene has been carried out over mono-, di- and tri-vanadium-substituted phosphomolybdic acid catalysts with aqueous hydrogen peroxide (aq. H2O2) as an oxidant in different solvents. Monovanadium-substituted phosphomolybdic acid catalyst was found to be better than other catalysts for the above reaction and acetonitrile was the suitable solvent. At the optimum temperature of 60 degreesC, the norbornene conversion was 70% and the selectivity for 2,3-epoxy norbornane was 58%. The side products were norborneols and 2-norbornanone. The lower selectivity of 2,3-epoxy norbornane with aq. H2O2 is attributed to the simultaneous formation of other products, norborneols and 2-norbornanone. The norborneols are formed from norbornene by acid-catalyzed reaction. Other oxidants like urea-hydrogen peroxide adduct (UHP) and tert-butyl hydrogen peroxide (TBHP) were also tested for norbornene oxidation reaction. With UHP, the conversion was almost same (69%) as that of aq. H2O2 reaction; however, 2,3-epoxy norbornane was the main product with >97% selectivity. Thus, the overall yield was 66.9% at 60 degreesC after 4 h. The high selectivity with UHP is attributed to the controlled release of H2O2, absence of water and less acidic nature of UHP. With TBHP the selectivity for the epoxide was >96%; however, the conversion was low (27%). A mechanism for the norbornene oxidation is believed to be proceeding via V(5+)-peroxo and V(4+)-superoxo intermediates. NMR, EPR and UV-vis spectroscopic techniques were employed to understand the reaction intermediates and reaction pathways. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: 2; 3-epoxy norbornane; aq. H2O2; epoxidation; EPR; NMR; norbornene; urea-H2O2 adduct; UV-Vis; vanadium-substituted phosphomolybdic acid

Oxovanadium(IV) complex of 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene for oxidation of benzoin - Maurya, Mannar R.; Sikarwar, Sweta; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Vanadyl sulphate reacts with 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene (PS-Hhebmz) cross-linked with 5% divinyl benzene to give PS-[VO(hebmZ)(2)]. Characterisation of the catalyst was carried out by IR, electronic and EPR spectroscopic studies, thermogravimetry, scanning electron micrographs and elemental analyses. Catalytic potential of the complex was tested for the oxidation of benzoin using tert-butyl hydroperoxide (TBHP) as an oxidant in methanol where benzil, methylbenzoate, benzoic acid and dimethylacetal were obtained as products. Various parameters such as different solvents and concentration of the substrate as well as oxidant have been taken into consideration for the maximum oxidation of the benzoin. Under optimised reaction conditions, a maximum of 98.9% conversion of the benzoin was achieved after 6 h of reaction time where selectivity of the obtained reaction products varied in the order: methylbenzoate (48.5%) > benzil (19.5%) > dimethylacetal (17.1%) > benzoic acid (11.5%). Neat complex was also prepared to compare its catalytic property with polymer-anchored one. EPR spectra of neat and polymer anchored catalyst are characteristics of V(IV) complexes with typical axial pattern and possible square pyramidal geometry. The identical EPR spectral patterns of both freshly prepared and recovered anchored catalysts indicate that the complex is stable and the coordination environment is retained at the end of the catalytic reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2-(alpha-hydroxyethyl)benzimidazole; oxidation of benzoin; polymer-anchored complex; Polystyrene; vanadium(IV) complex